Once failed to go abroad, Nur Khairiyah recipient of Royal Education Award Pingat Jaya Cemerlang now works in Germany - Rosidah, Hassan (2022)
PAYA BESAR, 5 November 2022 - The failure to continue study in Germany a long time ago has never discouraged Nur Khairiyah Hibatullah Md Rosley, 25 and has even given high motivation to continue to move forward and pursue dreams.